(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The satisfaction of customers and guests is crucial for the hotel and hospitality industry. Inadequate communication between hotel management and employees can have adverse effects on the customer experience, employee morale, and ultimately lead to a decline in profits. By investing in new communication technologies for hotels, you can ensure that your operations run smoothly and your guests are happy and satisfied. Respectively, organizational communication technologies have become an integral part of hotel management in recent years. With the increasing use of technology in the hospitality industry, hotels are now able to streamline their operations, improve guest experiences, and enhance their overall performance. The significance of communication in management cannot be overstated. Effective communication is essential for leaders to facilitate the accomplishment of an organization’s objectives. Without the ability to share information, people cannot collaborate, establish goals, and attain them. In this article, we will explore the role and application of organizational communication technologies in hotel management.